2021
DOI: 10.3390/molecules26071967
|View full text |Cite
|
Sign up to set email alerts
|

Poly Lactic Acid (PLA) Nanocomposites: Effect of Inorganic Nanoparticles Reinforcement on Its Performance and Food Packaging Applications

Abstract: Poly lactic acid (PLA) is a compostable, as well as recyclable, sustainable, versatile and environmentally friendly alternative, because the monomer of PLA-lactide (LA) is extracted from natural sources. PLA’s techno-functional properties are fairly similar to fossil-based polymers; however, in pristine state, its brittleness and delicacy during processing pose challenges to its potential exploitation in diverse food packaging applications. PLA is, therefore, re-engineered to improve its thermal, rheological, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 81 publications
1
41
0
Order By: Relevance
“…However, the industry has recently evolved to produce more biocompatible polymers called "bio inks" [8] [9]. These include polycaprolactone, polylactic acid (PLA) and polyglycolic acid (PGA) and are FDA-approved for biological use [5][10] [11]. Of these, PLA resin (e-resin PLA, eSun, China) was affordable and available in our region.…”
Section: Discussionmentioning
confidence: 99%
“…However, the industry has recently evolved to produce more biocompatible polymers called "bio inks" [8] [9]. These include polycaprolactone, polylactic acid (PLA) and polyglycolic acid (PGA) and are FDA-approved for biological use [5][10] [11]. Of these, PLA resin (e-resin PLA, eSun, China) was affordable and available in our region.…”
Section: Discussionmentioning
confidence: 99%
“…Despite PLA being extensively adopted, it still has drawbacks such as its cost and its structural breakability and fragility. Different approaches have been studied to improve its properties, such as the incorporation of nanoparticles [ 155 ].…”
Section: New Generations Of Plasticsmentioning
confidence: 99%
“… 1 , 3 , 18 Recent studies reported the effect of modifying the PLA structure by the introduction of different materials. Cellulose fibers, 15 , 19 22 silica nanoparticles, 1 , 4 , 9 , 10 , 14 , 20 , 23 30 and other organic compounds 16 , 31 39 have remarkably increased the mechanical, thermal, and barrier properties, reaching values close to current plastics. 16 , 40 Also, some studies analyzed the PLA crystallinity and how its variation produced an improvement in mechanical and barrier properties.…”
Section: Introductionmentioning
confidence: 99%
“… 12 16 However, its barrier properties need to be improved to allow the extensive commercial application of PLA, along other properties. 14 17 The general improvement of these important properties is still expensive. 1 , 3 , 18 Recent studies reported the effect of modifying the PLA structure by the introduction of different materials.…”
Section: Introductionmentioning
confidence: 99%